FMRP Modulates Activity-Dependent Spine Plasticity by Binding Cofilin1 mRNA and Regulating Localization and Local Translation. (6th April 2019) - Feuge, Jonas; Scharkowski, Franziska; Michaelsen-Preusse, Kristin; Korte, Martin
Abstract: Multiple variants of intellectual disability, e.g., the Fragile X Syndrome are associated with alterations in dendritic spine morphology, thereby pointing to dysregulated actin dynamics during development and processes of synaptic plasticity. Surprisingly, although the necessity of spine actin remodeling was demonstrated repeatedly, the importance and precise role of actin regulators is often undervalued. Here, we provide evidence that structural and functional plasticity are severely impaired after NMDAR-dependent LTP in the hippocampus of Fmr1 KO mice. We can link these defects to an aberrant activity-dependent regulation of Cofilin 1 (cof1) as activity-dependent modulations of local cof1 mRNA availability, local cof1 translation as well as total cof1 expression are impaired in the absence of FMRP. Finally, we can rescue activity-dependent structural plasticity in KO neurons by mimicking the regulation of cof1 observed in WT cells, thereby illustrating the potential of actin modulators to provide novel treatment strategies for the Fragile X Syndrome.